Edukasi Sedekah Melalui Sodaqoh Sampah Kelurahan Kapas Kecamatan Sukomoro Nganjuk - Alifatul Maula; Siti Kalimah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
The wider community environment has a different character and in awareness of the use of used bottles or plastic waste, they are still minimal in their utilization. Based on this context, this community assistance program is carried out and directed to provide community empowerment about the benefits of plastic waste as household income and or can be as an awareness of bersodaqoh. Mentoring also creates good cooperation and communication between the author and the community, as well as the participation of the Sukomoro subdistrict cotton village in succeeding this mentoring program. Most of the people participate in this program, namely in collecting used plastic bottles, they are very enthusiastic because they are encouraged to collect garbage as an embodiment of almsgiving. After the used plastic bottle or garbage is collected a lot, it will be sold and the proceeds from the sale will be allocated as compensation for orphans and shared alms to widowed mothers. It has the full support of the community in running this program. For that, the running of the Sodaqoh Sampah program is expected to be able to resuscitate people in other areas to give alms, because alms does not have to be with money and by collecting, and continue to be sold used bottles can increase the income of household needs.